Does festival-goer is a risk-taker? - Ismail, Khairiah; Abdullah, Nawal Hanim; Hassan, Hamimah; Zamzuri, Norol Hamiza (e-International Publishing House, 2021)
This paper examines festivalgoers' risk-taking behaviour, focusing on a Malaysian music festival. A qualitative methodology based on in-depth interviews with 15 music festival-goers. The respondents' risk-taking behaviour was examined using DOSPERT, including financial, health and safety, recreation, ethical, and social domains. The findings show that the previous music festival's risks did not affect festivalgoers' motivation to attend. A significant impact on government, organiser, and society. Respondents offered some guidelines for organising a music festival. Since very few papers examine the prospect of risk in music festivals, the adoption of DOSPERT provides much-needed rich and credible data.